ENDOTHELIAL DYSFUNCTION AND BLOOD VISCOSITY INPATIENTS WITH UNSTABLE ANGINA IN DIFFERENT PERIODS OF A SOLAR ACTIVITY - Parshina, S. S.; Tokaeva, L. K.; Dolgova, E. M.; Afanas'yeva, T. N.; Strelnikova, O. A. (Одеські астрономічні публікації, 2013)
The origin of hemorheologic and endothelial defects in patients with unstable angina (comparing with healthy persons) is determined by a solar activity period: the blood viscosity increases in a period of high solar activity in the vessels of small, medium and macro diameters, a local decompensate dysfunction of small vessels endothelium had been fixed (microcirculation area). In the period of a low solar activity there is an increase of a blood viscosity in vessels of all diameters, generalized subcompensated endothelial dysfunction is developed (on the background of the III phase blood clotting activating). In the period of a high solar activity a higher blood viscosity had been fixed, comparing with the period of a low solar activity.